Leading Change With Intelligence: The Power of Diagnosis in Creating Organizational Renewal. (December 2020) - Coruzzi, Celeste A.
The success of any organizational change effort relies first and foremost on expert diagnosis—the ability to gain intelligence about the system you are trying to change. The Burke–Litwin Model of Organizational Performance and Change, as developed by W. Warner Burke and George H. Litwin, represents one of a critical body of work contributing to the efficacy of leadership and its essential role in both diagnosing and managing organizational change from a holistic, open-systems view. An in-depth study of the model in practice is presented in the case of Electric Boat during a time of significant growth, technology adaptation, and demographic/attitudinal shifts in the workplace.